Allah made them all: quran stories for little hearts - Lockhat, Khadija; Negi, Devender (Goodword Books New Delhi, 2004)
Allah Made Them All: Quran Stories for Little Hearts is a delightful children's book that celebrates the diversity of creation, sharing engaging stories that highlight the wonders of the natural world and the importance of appreciating all of Allah's creations.